Postoperative outcome after palliative treatment of malignant pleural effusion. Issue 15 (15th June 2022) - Markowiak, Till; Ried, Michael; Großer, Christian; Hofmann, Hans‐Stefan; Hillejan, Ludger; Hecker, Erich; Semik, Michael; Lesser, Thomas; Kugler, Christian; Seifert, Sven; Scheubel, Robert
Abstract: Background: The objective of this nationwide, registry‐based study was to compare the two most frequently used procedures for the palliative treatment of a malignant pleural effusion (MPE) and to evaluate differentiated indications for these two procedures. Methods: This was a retrospective observational study based on data of the "PLEURATUMOR" registry of the German Society for Thoracic Surgery. Patients who were documented in the period from January 2015 to November 2021 and had video‐assisted thoracic surgery (VATS) talc pleurodesis or implantation of an indwelling pleural catheter (IPC) were included. Results: A total of 543 patients were evaluated. The majority suffered from secondary pleural carcinomatosis ( n = 402; 74%). VATS talc pleurodesis ( n = 361; 66.5%) was performed about twice as often as IPC implantation ( n = 182; 33.5%). The duration of surgery was significantly shorter in IPC‐patients with 30 min compared to VATS talc pleurodesis (38 min; p = 0.000). Postoperative complication rate was 11.8% overall and slightly higher after VATS talc pleurodesis ( n = 49; 13.6%) than after IPC implantation ( n = 15; 8.2%). After VATS talc pleurodesis patients were hospitalized significantly longer compared to the IPC group (6 vs. 3.5 days; p = 0.000). There was no significant difference in postoperative wound infections between the groups ( p = 0.10). The 30‐day mortality was 7.9% ( n = 41). Conclusion: The implantation of an IPC can significantly shorten the duration of surgery and the hospital stay. For this reason, the procedure should be matched with the patient's expectations preoperatively and the use of an IPC should be considered not only in the case of a trapped lung. Abstract : The aim of this study was to compare thoracoscopic talc pleurodesis and implantation of an IPC in the palliative treatment of MPE. It was found that implantation of an IPC can significantly shorten the duration of surgery and hospital stay. For this reason, the procedure should be matched preoperatively to the patient's expectations and the use of an IPC should be considered not only in the case of a trapped lung.